(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: to evaluate the occurrence and risk factors for the development of pressure injury (PI) in patients admitted in medical and surgical clinics and in observation at the emergency room of a university hospital. Methods: Cross-sectional, descriptive-exploratory, epidemiological study. Patients were assessed by physical examination three times a week for two consecutive months between June and November 2016. Results: the frequency of PI was 29% (n = 9) in the medical clinic, 16% (n = 4) in the surgical clinic and 53.8%(n = 7) in observation at the emergency room. According to the Braden scale, seven (30.4%) patients in the medical clinic presented high risk and two (25%) moderate risk; three (27.3%) patients from the surgical clinic presented a high risk and one (7.1%) moderate risk; and seven (58.3%) patients in observation at the emergency room were high risk. The risk factors associated with the participants who developed PI were: restriction in the bed, use of catheters or devices, vasoactive drug, diaper, mechanical ventilation, sedatives, unconsciousness, food fasting and hospitalization time over 10 days. Conclusion: there was a high frequency of PI in the medical and surgical clinics and in observation at the emergency room. Most patients were high risk for developing PI.